New Fowler Proficiency / Reading - Fowler W.S (New Editions, 2002)
This book provides comprehensive coverage of each part of the Reading Paper in the revised Cambridge Proficiency Examination. Education, The Arts, Work, History, Crime, House and Home, Relationships, Travel, Neighborhood, Leisure, Business, Health, Mysteries, Environment, Sport, Media, Appendices, Phrasal Verbs, Idiomatic Words and Phrases, Collocations and Common Combinations.